PENGARUH INDEPENDENSI AUDITOR DAN PROFESIONALISME AUDITOR TERHADAP KUALITAS AUDIT PADA BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA PERWAKILAN SUMATERA BARAT - Risma Dinda; Annisa Annisa (LPPM Universitas Bina Bangsa, 2024)
This research aims to test whether there is an regresion of auditor independence and auditor professionalism on audit quality at BPK of Sumatera Padang The population in this research are auditors who work at the Padang Financial Audit Agency (BPK). The samples used were 129 samples from the Financial Audit Agency (BPK) in Padang. The sampling technique uses a purposive sampling method. The research method used is quantitative with the data source in the form of primary data. The data analysis method uses multiple linear regression analysis with SPSS version 26. The results of this research provide empirical evidence that partially the auditor independence variable, auditor professionalism has a positive effect on audit quality. Simultaneously, the variables of auditor independence, auditor professionalism have a positive effect on audit quality